The effects of favipiravir on hematological parameters of covıd-19 patients - Yaylaci,Selçuk (2020)
SUMMARY INTRODUCTION This study aims to evaluate changes in hematological parameters after the follow-up of patients who received treatment with favipiravir due to COVID-19 infections. METHODS Sixty-two cases receiving favipiravir treatment for at least five days due to COVID-19 infection were evaluated retrospectively. Parameters including age, gender, nasopharyngeal swab positivity, and chronic diseases were analyzed. Hematologic parameters were analyzed before and after the treatment. RESULTS The mean age of the patients receiving treatment with favipiravir was 63.7±12.3 years. Nasopharyngeal swab positivity was detected in 67.7%. The most common comorbid conditions detected in patients were hypertension in 25 cases (40.3%) and diabetes in 16 cases (25.8%). In the statistical analysis of the hematological parameters before and after treatment with favipiravir, WBC, PT-PTT-INR levels were found to be unaffected; the mean RBC was found to have decreased from 4.33 ± 0.58 M/uL to 4.16 ± 0.54 M/uL (p:0.003); the median hemoglobin level was found to have decreased from 12.3 g/dl to 11.9 g/dl (p:0.041); the hematocrit level decreased from 38.1% ± 4.8 to 36.9% ± 4.2 (p:0.026); the median neutrophil count decreased from 4.57 K/uL to 3.85 K/uL (p:0.001); the mean lymphocyte count increased from 1.22 ± 0.53 K/uL to 1.84 ± 1.19 K/uL (p:0.000); and the mean platelet count increased from 244.1 ± 85.1 K/uL to 281.9 ± 103.3 K/uL (p:0.005). CONCLUSION We concluded that the pathological effect of treatment with favipiravir on the hematologic system was the suppression in the erythrocyte series, and there were no adverse effects in other hematologic parameters.